2020
DOI: 10.1017/s0007114520003992
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast is associated with the presence of cardiometabolic risk factors in adolescents: Study of Cardiovascular Risks in Adolescents – ERICA

Abstract: Breakfast is considered as the most important meal of the day. The habit of skipping this meal in adolescence tends to remain until adulthood and has been associated with cardiometabolic risk factors. This study estimated the prevalence of skipping breakfast and its association with cardiometabolic risk factors. This is a cross-sectional study with data from the Study of Cardiovascular Risks in Adolescents (ERICA), with a nationally representative sample of 36,956 Brazilian adolescents, aged 10 to 17 years, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
0
24
0
7
Order By: Relevance
“…13 Além disso, a omissão e a baixa frequência de refeições, observadas entre adolescentes de famílias monoparentais dos estudos incluídos na presente revisão, podem predizer a continuidade deste comportamento na idade adulta 30 e têm sido associadas ao excesso de peso em adolescentes. 1,[40][41][42] Timlin et al 43 realizaram estudo longitudinal com cinco anos de seguimento, avaliando 2.216 adolescentes e verificaram que o consumo frequente de café da manhã foi um marcador de estilo de vida saudável, sendo inversamente associado ao ganho de peso. Além disso, o consumo frequente de café da manhã associou-se à ingestão de maiores quantidades de energia, carboidratos e fibras, e menor de gordura saturada.…”
Section: Discussionunclassified
“…13 Além disso, a omissão e a baixa frequência de refeições, observadas entre adolescentes de famílias monoparentais dos estudos incluídos na presente revisão, podem predizer a continuidade deste comportamento na idade adulta 30 e têm sido associadas ao excesso de peso em adolescentes. 1,[40][41][42] Timlin et al 43 realizaram estudo longitudinal com cinco anos de seguimento, avaliando 2.216 adolescentes e verificaram que o consumo frequente de café da manhã foi um marcador de estilo de vida saudável, sendo inversamente associado ao ganho de peso. Além disso, o consumo frequente de café da manhã associou-se à ingestão de maiores quantidades de energia, carboidratos e fibras, e menor de gordura saturada.…”
Section: Discussionunclassified
“…Despite the fact that many schools have breakfast programs, our results are consistent with reports that many students still skip breakfast [47] and the prevalence of this behaviour appears to be increasing. Breakfast skipping has been linked to reduced daily dietary intakes [48] and increased cardiometabolic risk [49]. Furthermore, those who skip breakfast may engage in irregular eating patterns (such as late night snacking), which can have a negative impact on sleep quality [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been studies on the increasing prevalence of breakfast skipping, such as that from the United States, which reported that the prevalence has increased over the past 50 years, with up to 23.8% of young people skipping breakfast daily [ 15 , 16 ]. It has been reported that skipping breakfast is related to adolescent cardiometabolic risk factors such as an altered lipid profile [ 17 ]. Previous studies have found that metabolic syndrome is inversely related to breakfast consumption frequency [ 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%